METHYLPHENIDATE EXPOSURE DURING PERIPUBERTAL PHASE AFFECTS LEARNING AND MEMORY OF ADULT RATS (Arquivos do Mudi, 2023)
Methylphenidate (MPH) is the active ingredient in Ritalin, although effective in treating ofthe attention deficit hyperactivity disorder (ADHD), its neurostimulation action is attractiveamong students in order to increase the focus or improving student performance. In context ofthe Developmental Origins of Health and Disease (DOHaD) concept, states that insults incritical phases of development, as the peripubertal period, may program the organism todysfunctions in adulthood. The aim of this work was to investigate the impact of peripubertalMPH exposure on learning and retrograde memory in adult rats. Male Wistar rats wereexposed to MPH (5 mg/kg) from post-natal day (PN) 30 until PN60 (MPH). Control animalsreceived 0.9% saline (Sal). At PN60, learning was evaluated true 10 days in an eight-armelevated maze and at PN120 retrograde memory. At PN60, MPH group showed a delay of61% in the latency, an increase of 100% in the number of errors and 200% in the number ofrepetition errors when compared to the Sal group, until the day 5 of learning period (p=0.004).After the washout period, at PN120, the MPH group showed an increase of 37% in thelatency, 49% in the number of errors of reference and 600% in the number of repetition errorscompared with the Sal group (p=0.001, p=0.004 and p=0.01). Exposure to MPH duringperipubertal phase decreases learning and memory in adult male Wistar rats.